Tafsir atas Hukum Murtad dalam Islam - Abd. Moqsith (AHKAM : Jurnal Ilmu Syariah, 2013)
Abstract: An Exegesis on Apostasy Law in Islam. A discussion on apostasy almost spread throughout the corpus of Islamic law, both past and present. The concept of apostasy is now facing a serious challenge in a society that supports freedom of religion. Modern society tends to be of the opinion that the choice of individuals to enter or exit from a religion is a private matter that should not be interfered with by any authority. While Islamic jurisprudence, particularly that which is mainstream, further criminalizes apostates. Opening the entire argument about the concept of apostasy is a necessity. There are several verses of the Koran that speak of apostasy and there are various exegesis of apostasy which are discovered by scholars. There are scholars who criminalize apostates by referring to a Hadith, but there are also scholars who reject to have evidence of these Hadith.Keywords: apostasy, conversion, religious freedomAbstrak: Tafsir atas Hukum Murtad dalam Islam. Bahasan murtad hampir merata di seluruh korpus mengenai hukum Islam, baik dulu maupun sekarang. Konsep murtad kini menghadapi tantangan serius di tengah masyarakat yang mendukung kebebasan beragama. Masyarakat modern cenderung berpendirian bahwa pilihan seseorang untuk masuk atau keluar dari suatu agama adalah masalah privat yang tidak boleh diintervensi otoritas apapun. Sementara fikih Islam, terutama yang mainstream, lebih banyak mengkriminalkan orang murtad. Membuka seluruh argumen tentang konsep murtad adalah keniscayaan. Ada beberapa ayat Alquran yang membicarakan murtad dan ada beragam tafsir murtad yang dikemukakan para ulama. Ada ulama yang mengkriminalkan orang murtad dengan merujuk suatu Hadis, tetapi ada juga ulama yang menolak ber-hujjah dengan Hadis tersebut.Kata Kunci: murtad, pindah agama, kebebasan beragamaDOI: 10.15408/ajis.v13i2.940